Estudio de adaptación de siete pastos y tres mezclas forrajeras con la utilización de lactofermentos, en el barrio San Francisco, Parroquia Toacazo, Cantón Latacunga, Provincia De Cotopaxi, 2019-2020. - Alvarado Alquinga, Luis Calixto (2020)
The present research was carried out in San Francisco Neighborhood, located in Toacaso Parish, Latacunga Canton, Cotopaxi Province, with UTM latitude coordinates: 9921925.07 S longitude: 744876.27 Or at a 3,300 height masl. The goal was to determine the grass that presents better adaptability to the sector. Seven pastures and three forage mixtures were used, with lacto-ferment application. The experimental design implemented was divided into plots (A x B) which revealed twenty treatments with three repetitions. The variables which were analyzed: plant height, cover, microorganisms and soil fungi. The results showed: the grass with the best agronomic behavior, the T5 treatment (chicory) 40.13 cm and 46.98 cm at 43 and 50 days. Tukey tests on 5% can be determined that the lacto ferment performed in a representative way between the treatments and the soil’ fertility. The grass with the highest coverage percentage at 57 days for factor A (grasses), was the T5 treatment (chicory) the best with 88.50%. The results obtained from the biological composition of the lacto ferment did not reveal the existence of microorganisms, while the chemical analysis reveals the macro elements presence such as: N (0.002g 100ml), P (0.03g 100ml), K (1.19g 100ml) and micro elements such as: B (0.31ppm), Zn (4074), Cu (1.16 ppm). The elements mentioned before are essential for the soil and therefore for the grasses growth. The soil in microbiological analysis shows difference between yeasts and fungi. The highest rank in the count of colony forming units per gram (CFU / g) of fungi present in the soil, were the treatments T7 (oatmeal) and T4 (reygrass), and for the count of yeasts; the treatments, T7 (oatmeal) and T9 (vicia-avena).